E-Book as Educational Media ‘Aku dan Kehamilan Sehat-Ku’ : Narrative Review - Fatiah Handayani; Anggie Yuliyati; Cindi Zaenudin; Syifa Azzahra (STIKes Patria Husada Blitar, 2021)
Technological developments have affected the method of providing education in every field. The development of health education media is very helpful in increasing understanding of healthy living, as the process of pregnancy is a natural process. Hormonal changes that cause various kinds of complaints or discomfort will affect the baby if it is not addressed properly. The purpose of this research was to examine the results of research on the use of digital books or electronic books (e-books) in providing information about discomfort in pregnancy.This research used Narrative Review method, namely examining research articles. The research articles were obtained using the e-book, pregnancy, discomfort keywords in pregnancy from the Google Scholar, PubMed, Scopus and Wos databases. There were 30 articles obtained Â with 19 articles that were in accordance with the research objectives. It can be concluded that that there is a potential to develop e-book media that is modified with multimedia to be used as a media for health education about pregnancy and its discomfort.